Small Gap Dynamics in High Mountain Central European Spruce Forests—The Role of Standing Dead Trees in Gap Formation - Denisa Sedmáková; Peter Jaloviar; Oľga Mišíková; Ladislav Šumichrast; Barbora Slováčková; Stanislav Kucbel; Jaroslav Vencurik; Michal Bosela; Róbert Sedmák (Plants)
Gap dynamics are driving many important processes in the development of temperate forest ecosystems. What remains largely unknown is how often the regeneration processes initialized by endogenous mortality of dominant and co-dominant canopy trees take place. We conducted a study in the high mountain forests of the Central Western Carpathians, naturally dominated by the Norway spruce. Based on the repeated forest inventories in two localities, we quantified the structure and amount of deadwood, as well as the associated mortality of standing dead canopy trees. We determined the basic specific gravity of wood and anatomical changes in the initial phase of wood decomposition. The approach for estimating the rate of gap formation and the number of canopy trees per unit area needed for intentional gap formation was formulated based on residence time analysis of three localities. The initial phase of gap formation (standing dead tree in the first decay class) had a narrow range of residence values, with a 90–95% probability that gap age was less than 10 or 13 years. Correspondingly, a relatively constant absolute number of 12 and 13 canopy spruce trees per hectare died standing in 10 years, with a mean diameter reaching 50–58 cm. Maximum diameters trees (70–80 cm) were represented by 1–4 stems per hectare. The values of the wood-specific gravity of standing trees were around 0.370–0.380 g.cm−3, and varied from 0.302 to 0.523 g.cm−3. Microscopically, our results point out that gap formation is a continuous long-lasting process, starting while canopy trees are living. We observed early signs of wood degradation and bacteria, possibly associated with bark beetles, that induce a strong effect when attacking living trees with vigorous defenses. New information about the initial phase of gap formation has provided a basis for the objective proposal of intervals and intensities of interventions, designed to promote a diversified structure and the long-term ecological stability of the mountain spruce stands in changing climate conditions.